Evaluation of Selected Soil Physical Properties in Oil Palm, Rubber, and Forest Land in Mukomuko Regency - Nurwanto, Ahmad; Hermawan, Bandi; Widiyono, Heru; Sulistyo, Bambang; Hindarto, Kanang Setyo (TERRA : Journal of Land Restoration, 2025)
This study investigates the influence of land use on soil physical properties and horizon thickness in Mukomuko Regency, Indonesia, to assess the impacts of agricultural practices on soil quality. Conducted between February and April 2020, the research utilized a nested design across four districts, with laboratory analyses performed at the Soil Science Laboratory, Bengkulu University. Land use types evaluated included oil palm, rubber, and natural forest. Variables measured comprised soil structure, horizon thickness, aggregate stability, bulk density (BD), texture, and organic carbon (C-organic). Statistical analysis (ANOVA, p < 0.05) revealed significant effects of land use on BD, C organic content, and soil texture, whereas aggregate stability was not significantly influenced by vegetation type or depth. Forest soils exhibited the highest C-organic content (5.78%) and lowest BD (0.82 g cm⁻³), contrasting with oil palm soils, which had the lowest C-organic content (4.22%) and highest BD (0.86 g cm⁻³). Texture analysis showed forest soils had higher sand (19.69%) and clay (50.20%) fractions, while rubber land had the highest silt content (57.59%). Soil physical properties generally declined with depth under rubber and oil palm but fluctuated in forest soils. These results suggest that vegetation type significantly affects soil quality, with forest ecosystems maintaining superior soil conditions compared to intensively managed agricultural systems. Adoption of sustainable land management practices is essential to mitigate soil degradation and enhance long-term productivity.